2023
DOI: 10.3390/ijerph20095680
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine among Adults Living in America during the COVID-19 Pandemic

Abstract: Background and Objectives Telemedicine can expand healthcare access to populations, but relying on technology risks a digital divide. Therefore, it is important to understand who utilizes telemedicine. This study explores telemedicine usage across socio-demographic groups in the United States during COVID-19. Methods Data came from the Household Pulse Survey (HPS) between 14 April 2021, to 11 April 2022. HPS is a rapid online response survey that assesses household experiences during COVID-19. We calculated de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Additionally, telehealth use was highest among those living in the Northeast and West regions [7]. These studies were conducted on large sample sizes of overall patients, enabling the detection of small differences [7,12]. The discrepancy between our results and those of others could be attributed to the current study's smaller sample size vs. studies with larger sample sizes [7] or to different researched populations (overall patients vs. informal caregivers).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Additionally, telehealth use was highest among those living in the Northeast and West regions [7]. These studies were conducted on large sample sizes of overall patients, enabling the detection of small differences [7,12]. The discrepancy between our results and those of others could be attributed to the current study's smaller sample size vs. studies with larger sample sizes [7] or to different researched populations (overall patients vs. informal caregivers).…”
Section: Discussionmentioning
confidence: 66%
“…The majority of the existing body of knowledge on telehealth utilization and quality, particularly related to sociodemographics, is based on the overall patient population [7][8][9][10][11][12]. Here, among informal caregivers, the comparative analysis between telehealth users and non-users revealed that age, gender, health insurance, and race/ethnicity were significantly associated with telehealth utilization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curioso et al [ 5 ] discuss the difficulties of implementing telemedicine in Peru and its importance during the COVID-19 pandemic. Hung et al [ 6 ] studied the characteristics of telemedicine users during the COVID-19 pandemic in the United States. They concluded that the use of telemedicine was higher among the elderly, blacks, college-educated, and disabled.…”
Section: Introductionmentioning
confidence: 99%